Телефон и другие сказки - Чуковский Корней Иванович (Читаем сами без мамы, 2021)
Экземпляры: ДО мл.аб. (2021) / Инвентарный номер: 57246 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ч-88 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=411.2)6